Sistem Pengunci Pintu Dengan Sidik Jari Menggunakan Arduino - Sahril, S; Suppa, Rinto; Muhallim, Muhlis (STIKOM Tunas Bangsa Pematangsiantar, 2022)
The purpose of this research is to create and implement a door lock system with fingerprints using Arduino in the hardware laboratory at the engineering faculty of the informatics engineering study program, Andi Djemma Palopo University. Lab users, in this case the lab head and assistant head of the lab, can put their finger on the sensor if they want to open the door. The door will open if the fingerprint that is pasted is the same as the fingerprint data of the lab user, and with a display on the 16x2 LCD which states that the fingerprint that is attached is suitable / not. The research method in this thesis includes analysis, system design, mechanical manufacturing, prototype simulation and implementation. In designing the Fingerprint Door locking system using Arduino, the At-mega 328 microcontroller is used to control selenoid as a door lock and several components needed in the design of security, including: arduio uno at-mega 328, fingerprint sensor, 16x2 LCD, adapter , solenoid, relay, push button, and breadboard. Based on the tests that have been carried out, it can be concluded as follows: this equipment has been tested and can be used to help the security system at the lab door by using a fingerprint. The fingerprint used to open the solenoid is a fingerprint that has a valid fingerprint pattern that has been registered previously. The results of usability testing are 89.8% of the tests carried out on students who use this locking system, so that it can be said to meet usability standards